First report of olive anthracnose caused by Colletotrichum gloeosporioides in Tunisia - Rhouma, Ali; Triki, Mohamed Ali; Msallem, Monji (Phytopathologia Mediterranea, 2010)
Ripe and overripe olive fruits (cv. Meski, Manzanilla and Picholine) showing circular spots 1 to 10 mm in diameter, slightly depressed and reddish-brown in color, were collected from local markets and orchards located in the regions of Takelsa, Zarzis and Rgueb in Tunisia. Colletotrichum gloeosporioides was isolated from symptomatic fruits and Koch’s postulates were fulfilled. This is the first report of Colletotrichum gloeosporioides causing anthracnose of olives in Tunisia.